The Mediating Role of Task Commitments on The Influence of Leaders Integrity on Job Performance Study at Tax Office in South Tangerang City - Muhtarom (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to analyze the contribution of leader integrity and task commitment in influencing employee performance. The study used a quantitative approach involving 93 employees of the tax office in South Tangerang City. Collecting data using a Likert scale questionnaire and analyzed using path analysis. The research findings indicate that the leader integrity and task commitment factors have a positive and significant influence on employee performance. Leader integrity is also known to have a significant influence on task commitment. Another finding shows that task commitment plays a role in mediating the influence of leader integrity on job performance. Based on these results, it is necessary to improve the integrity of the leadership and strengthen the task commitment to optimize job performance